2019
DOI: 10.3390/v12010012
|View full text |Cite
|
Sign up to set email alerts
|

The Zebrafish Xenograft Platform—A Novel Tool for Modeling KSHV-Associated Diseases

Abstract: Kaposi’s sarcoma associated-herpesvirus (KSHV, also known as human herpesvirus-8) is a gammaherpesvirus that establishes life-long infection in human B lymphocytes. KSHV infection is typically asymptomatic, but immunosuppression can predispose KSHV-infected individuals to primary effusion lymphoma (PEL); a malignancy driven by aberrant proliferation of latently infected B lymphocytes, and supported by pro-inflammatory cytokines and angiogenic factors produced by cells that succumb to lytic viral replication. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Our data demonstrate that BCP-ALL cells find the pericardial cavity to be a more hospitable environment than the yolk sac. Interestingly, the group of Jason Berman, who demonstrated feasibility of T-cell ALL engraftment into the yolk sac of zebrafish embryos in 2015 [21], recently reported that the zebrafish embryonic yolk sac actually provides a hypoxic environment for graft cells [32]. The hypoxic conditions might explain why any BCP-ALL cells transplanted into the yolk sac survived.…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrate that BCP-ALL cells find the pericardial cavity to be a more hospitable environment than the yolk sac. Interestingly, the group of Jason Berman, who demonstrated feasibility of T-cell ALL engraftment into the yolk sac of zebrafish embryos in 2015 [21], recently reported that the zebrafish embryonic yolk sac actually provides a hypoxic environment for graft cells [32]. The hypoxic conditions might explain why any BCP-ALL cells transplanted into the yolk sac survived.…”
Section: Discussionmentioning
confidence: 99%
“…In another experiment on tumor cells implanted into the yolk sac, researchers discovered that the hypoxic environment of the yolk sac may simulate the tumor microenvironment of some human tumors due to the lack of vascularization. They further found that the proliferation of primary effusion lymphoma cells in xenografts requires a hypoxic environment to stimulate eukaryotic translation initiation factor 4E2 (elF4E2) (Pringle et al, 2019 ).…”
Section: The Zebrafish Model In Studies Of the Tumor Microenvironmentmentioning
confidence: 99%
“…For both, the same pattern of metastatic spread was reported, which is analogous to stage IV disease [ 14 ]. KSHV (Kaposi’s sarcoma-associated herpesvirus)-infected PEL (primary effusion lymphoma) cells injected into the yolk sac of larvae indicated proliferation and the embryos tolerated xenotransplantation [ 15 ]. Non-small cell lung cancer (NSCLC) H1299 (p53-deficient) and A549 (p53-wild type) cell lines were xenografted into larval stage [ 16 ], as well as osteosarcoma (U2-OS) cells [ 17 ].…”
Section: Disease Induction: How To Create a Fish Modelmentioning
confidence: 99%